Rastreio de sarcopenia em pessoas idosas assistidas na Atenção Primária à Saúde - Oliveira, Francisco Gerlai Lima (2023)
During the aging process, several changes occur in the body composition of individuals that result in a decrease in muscle mass, strength and function, characterizing sarcopenia, a disease that favors functional decline, the risk of falls and morbidity and mortality. The objective was to track signs suggestive of sarcopenia and associated factors in elderly people assisted in Primary Health Care. Epidemiological, observational, cross-sectional study carried out with 385 elderly people. We included individuals aged 60 years or older, seen at a Primary Health Care Unit, and excluded those who did not meet the cut-off points in the Mini Mental State Examination (MMSE), had diagnoses and clinical signs suggestive of dementia, Parkinson's disease patients, stroke sequelae, bedridden individuals, and those with limb amputations. Data collection occurred from September 2022 to March 2023, in six Primary Health Care Units in the municipality of Tauá - CE. We used the Sociodemographic, Clinical and Anthropometric Data Form, the Mini Nutritional Assessment (MAN®), the International Physical Activity Questionnaire (IPAQ) adapted for elderly people and the Simple Questionnaire to Rapidly Diagnose Sarcopenia (SARC-F). The data were grouped and statistically analyzed using the Statistical Package for the Social Science (SPSS®) version 22.0 software, through descriptive analysis and associations between the outcome variable (suggestive of sarcopenia) and the independent variables through the Chi-square and Fisher's Exact tests with a significance level of 5% (p <0.05). The research was approved by the Research Ethics Committee of the Universidade Federal do Ceará with opinion 5.632.551 and CAAE: 60171622.7.0000.5054. The results showed that the mean age was 71.62 (±8.464) years, 55.6% were female, 60.5% illiterate, 75.3% were catholic, 66.5% were married/stable union, 91.7% had family income ranging from 1 to 2 minimum wages, 81.3% lived with the family, 64.4% had no paid occupation, 76.4% had suffered falls in the last 12 months, 73, 73.5% had comorbidities, systemic hypertension being the most prevalent (62.6%), 42.1% were eutrophic according to the body mass index, 85.2% had calf circumference equal to or greater than 31 cm, 93% were in normal nutritional status, 63.1% were sufficiently active, and 18.7% showed signs suggestive of sarcopenia. There was a significant association between signs suggestive of sarcopenia and age (p=<0.001), sex (p=<0.001), marital status (p=0.003), being retired (p=0.024) and having an occupation (p=<0.001), occurrences of falls (p= 0.002), number of falls (p=0.008), presence of comorbidities (p= 0.003), hypertension (p= 0.003), osteoarticular diseases (p=0.024) and heart diseases (p= 0.013), nutritional assessment (p=0.043) and physical activity (p=<0.001). The results are relevant and unprecedented for the elderly population, with information that may support the creation of public policies and health care programs for the elderly, in addition to encouraging nurses and other professionals in Primary Health Care to act on the subject and use the screening tools for sarcopenia in their clinical practice, enabling interventions, early detection actions of sarcopenia and health promotion of the elderly.